Power management of multi-source network hydraulic system with multiple actuators. (1st November 2020) - Yao, Jing; Wang, Pei; Yin, Yuxin; Li, Mandi; Li, Yao
Highlights: A multi-source hydraulic architecture is presented for high energy efficiency. The power management of this system can reduce power consumption. The switching supervisory controller is proposed for selecting the power modes. Logical threshold control is designed for different power modes switching. Experiments show that about 60% input energy can be reduced from the engine. Abstract: The mismatch between the load and pump sources and the restriction of energy recovery lead to large energy losses and lower energy efficiency in high power multi-actuator hydraulic systems. To obtain high energy efficiency, this paper develops a Multi-Source Network Hydraulic System (MSNHS) with multiple actuators and a corresponding power management strategy (PMS) to reduce the throttling losses and recover energy. The multiple energy-saving power modes based on the path of power transmissions, composed of different combinations of six power units with energy conversion and transfer, are implemented on MSNHS to supply and regenerate or recover power for various load conditions. Thus, the power consumption models of each power unit are established to analyze the power consumption characteristics for itself and power modes. On this basis, the switching supervisory controller is proposed to select an optimal mode for the current condition by utilizing an objective optimized function of minimal power consumption. Besides, the switching rules among power modes are designed, and the logical threshold control is presented for the multi-mode switching under different working conditions. The combination of the switching supervisory controller of optimal mode and the logical threshold control realizes the power management of the MSNHS with multiple actuators to accommodate with time-varying load and recover potential energy. The experimental validation is conducted on the MSNHS platform by simulating a 90° truck-loading cycle of the excavator. Experimental results demonstrate that the PMS applied to the MSNHS can downsize engine input power by up to 60.27% compared with the theoretical calculation of conventional one, and then improve overall system energy efficiency.